Diagnósticos dos aspectos do meio físico em áreas de manguezal, Parque Piaçabuçu - Praia Grande - SP. Sua relação com a ocupação por favelas - Luz, Normélia Carvalho (Universidade Federal de São Carlos, 2005)
The present study has as an overall goal the systematization of data on physical and biological mean aspects (vegetation, geology, hydrography, climate and topography) of the city of Praia Grande/SP, focusing on slum-occupied mangrove areas, generated through a soil usage guidelines assessment that shall work as a helpful tool in environmental planning of the above mentioned city. The historical process of the town s occupation to the local population s needs, the involved government spheres, the participation of non-governmental organizations, among other topics, will be approached with the final goal of contextualizing the physical aspects in question. As specific goals, the following will be elaborated: a flowchart of the influential factors of mangrove area slum populations, approaching the negative aspects of such a situation, as well as a potential usage guidelines assessment for uses that equalize the impacts of an area-planned environmental intervention.
Keywords: Manguezais; Proteção ambiental; Favelas; Resíduos industriais; Ocupação urbana desordenada; Mangroves; Preservation area; Shantytown; Environment; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS